Caracterización técnico productiva de establecimientos lecheros de la Región Pampeana Argentina - Engler, Patricia Laura; Cuatrin, Alejandra (Observatorio de la Cadena Láctea Argentina (OCLA); INTA, 2024)
Supervisores: • Marina Maekawa (Oeste; Bs As) • Magdalena Marino (Abasto Norte, Abasto Sur y Mar y Sierra; Bs As.) • Mónica Moretto (Villa María y Sur; Córdoba), • Alejandro Centeno (Noreste; Córdoba), • Gustavo Almada y Patricia Engler (Santa Fe) • Gabriela Litwin (Entre Ríos)